EVOLUTION OF PHANEROZOIC MIOSPORES AND MAIN STRIATION TYPES - Podgainaya N.N. (My University, 2004)
Morphogenetic peculiarities of exine striation types characteristic of the Phanerozoic miospores are discussed. During the period over 400 m.y. long, terrestrial plants produced 21 types of miospores with variably striated exine. Most of them originated in the Devonian and Permian epochs, while afterward the striation development decelerated so that younger forms are characterized in general by previous striation patterns. Among Triassic striate miospores there are two new types only, whereas Jurassic and Cretaceous epochs produced one new type each. Representatives of the Paleogene, Neogene-Quaternary, and Recent miospores inherit the striation types each characteristic of older taxa. The evolution of striate miospore was of the iterative type, as it follows from changes in disposition of striate sculptural elements. The evolution of land vegetation was accompanied by recurrent development of some striation types in the course of appearance of new plant and miospore taxa. Main morphotypes of striate miospores and their time succession are described. Origination and extinction of different striate morphotypes, which are confined to certain stratigraphic units, are recorded in a strict chronological succession. Type species of striate miospores typical of main Phanerozoic stratigraphic units and their stratigraphic ranges are characterized.